A Review of Nanotechnology Application for Seawater Desalination Process - Jordan, Evan; Jessica, Jessica; Martin, Martin; Suryajaya, Tommy; Hakeem, Muhammad Hilmy; Nugraha, Tutun; Listyorini, Niken Taufiqurrahmi (Surya University, 2016)
As freshwater resource decreasing rapidly due to high rate of human population growth, many researchers have done studies to develop methods for producing freshwater supply. Seawater desalination is one of the method that has the credibility to be implemented. However, conventional seawater desalination processes suffer from a number of problems related to energy efficiency and cost. In spite of this, nanotechnology has been applied to the process. In this paper, we give an overview and explanations concerning the roles of nanotechnology in seawater desalination processes which consist of pretreatment, reverse osmosis (RO), and disinfection. In addition, the comparisons between conventional and nanotechnology-applied processes as related to its efficiency and effectiveness are also provided.